ASPECTOS EPIDEMIOLÓGICOS DA INFECÇÃO POR LEPTOSPIRA SPP. EM FELINOS DOMÉSTICOS (FELIS CATUS) APARENTEMENTE SADIOS DA REGIÃO METROPOLITANA DE GOIÂNIA , GOIÁS - PARREIRA, Ivonete Maria (2009)
In felines, the leptospirosis is described commonly as of rare occurrence, in spite of inquiries sorologic accomplished at several countries they have already registered positive reactions in these you encourage. In this research it was aimed at to evaluate the presence of antibodies anti-Leptospira spp in samples of serums of domestic felines originating from of the areas of Goiânia and of Aparecida from Goiânia, Goiás, Brazil, besides evaluating biochemical parameters and of investigating decisive factors associated to the infection. Sanguine serums of 330 domestic felines were analyzed seemingly healthy, being 113 of domiciled animals in different neighborhoods of Goiânia and 217 of individuals picked up to the Center of Zoonosis of Control (CCZ) of Aparecida from Goiânia. The research of antibodies anti-Leptospira spp. it was accomplished through the test of microscopic agglutination (SAM) with alive antigens. Parallel, dosagens were proceeded of range-glutamiltransferase (GGT), alkaline phosphatase (FA), urea and creatinine. The presence of agglutinative antibodies was detected in 23 animals (6,96%), with titles that varied from 1:100 to 1:800, with predominance of co-agglutinations (7,76%) and of the sorovars Cynopteri and Djasiman. In Goiânia they were identified 10 animals (8,84%) positive seruns, while in Aparecida from Goiânia 13 were detected (5,99%) positive seruns. Reactions were verified for the sorovars Australis, Bratislava, Butembo, Castellonis, Canicola, Cynopteri, Djasiman, Hebdomadis, Copenhageni, Icterohaemorrhagiae, Pomona, Pyrogenes, Hardjo, Patoc, with minimum title of 1:100. significant difference was not observed by the test of regression logistics, between the positive and biochemical alterations as well as between positive and age and sex of the animals. Biochemical alterations and age came related. The obtained results served as parameters for the evaluation of the infection in domestic felines in the study area, contributing to the elucidation of epidemic aspects and for the control of the zoonosis, seeking to reduce the risk to the human health and your impacts sanitary, social and economical.